COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN E-PARKIR TEPI JALAN UMUM (TJU) ZONA 1 KOTA SURABAYA - Sunariyah Duwi Wantika; Deasy Rizki Masruroh; Diana Hertati (JOSH: Journal of Sharia, 2026)
The implementation of e-parking for Public Roadside Parking (TJU) Zone 1 in Surabaya City faces challenges such as high complexity of vehicle mobility and obstacles in digital adaptation by field implementers. The success of this innovation depends not only on technological advancement but also on the collaborative synergy among the government, private sector, parking attendants, and the community. This study aims to analyze the collaborative governance process in the management of e-parking in TJU Zone 1, Surabaya City. The research utilizes a descriptive qualitative method, collecting data through interviews, observations, and documentation. Data analysis applies the interactive model of Miles, Huberman, and Saldaña—comprising data condensation, data display, and conclusion drawing—which is then examined using Ansell and Gash's framework. The results indicate the mapping of five collaborative dimensions: (1) face-to-face dialogue was conducted through FGDs and monitoring, although information distribution remains uneven; (2) trust building was pursued through increased profit-sharing, yet some parking attendants still view digital devices as an extra workload; (3) commitment to process is demonstrated by actors consistently fulfilling their respective roles; (4) shared understanding was well achieved between the government and technology providers, but the long-term benefits are not yet fully comprehended by all parking attendants; and (5) intermediate outcomes are realized through system transparency and the availability of cashless alternatives, despite non-maximal adoption. This study recommends direct technical assistance for parking attendants to reduce technological resistance, as well as the implementation of specific campaigns/incentives for users to accelerate cashless payments